2020
DOI: 10.1155/2020/5637864
|View full text |Cite
|
Sign up to set email alerts
|

Mining miRNAs’ Expressions in Glioma Based on GEO Database and Their Effects on Biological Functions

Abstract: Purpose. To mine miR expression in glioma based on the Gene Expression Omnibus (GEO) database and to explore its effects on biological functions. Methods. Differentially expressed miRs in glioma-related chips were found out based on the GEO database. Fifty patients with glioma treated in our hospital from February 2012 to July 2013 (observation group, OG) and a further 50 healthy people undergoing physical examinations (control group, CG) were enrolled. miR-873-5p expression in serum and in U87, T98G, U251, LN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…High WHO tumor grade indicates progressive and aggressive glioma with dangerous and unpredictable consequences (51). Tumor diameter and lymph node metastasis are both valuable prognostic indicators for patients with glioma (52). Recent studies have reported that LINC01138 overexpression resulted in a poor overall survival rate and progression-free survival rate in patients with hepatocellular carcinoma (HCC) (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…High WHO tumor grade indicates progressive and aggressive glioma with dangerous and unpredictable consequences (51). Tumor diameter and lymph node metastasis are both valuable prognostic indicators for patients with glioma (52). Recent studies have reported that LINC01138 overexpression resulted in a poor overall survival rate and progression-free survival rate in patients with hepatocellular carcinoma (HCC) (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, microRNA (miR)-873-5p is a main member of the miR-873 family [ 4 ]. A recent study has proved the inhibiting effect of miR-873-5p in glioma cell proliferation and invasion and the promoting effect on cell apoptosis [ 5 ]. Meanwhile, miR-873-5p can repress GBM cell growth and migration, but inhibition of miR-873-5p shows opposite effects [ 6 ].…”
Section: Introductionmentioning
confidence: 99%